1999
DOI: 10.1136/gut.44.3.372
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of rectosigmoid adenomatous polyps in subjects without prior colorectal adenoma or cancer: a prospective cohort study

Abstract: Background-Subjects without known colorectal adenomas or cancer constitute a large majority of the population where 85% of all cases of colorectal cancer are thought to occur. Consequently these people should be considered for screening to decrease mortality from colorectal cancer in the general population. Aims-To estimate the incidence rate of rectosigmoid adenomas in these subjects. Methods-Subjects without adenomas or cancer at a previous examination which had visualised the rectosigmoid underwent a fibre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
1
3
1
Order By: Relevance
“…For studies involving flexible sigmoidoscopy and colonoscopy far fewer randomized controlled trials were available. However, examining the endoscopic outcomes (adenoma, advanced adenoma, colorectal cancer detection and adverse event rates) for non-physicians performing flexible sigmoidoscopy and colonoscopy we discovered that these outcomes for nonphysicians were in line with published data on physicians[4551] suggesting that the patients included in our studies were very likely similar to the patients included in other studies involving physicians performing endoscopy. Finally, minimal data was available on the optimal method used to train non-physicians, but data suggests it may be comparable to the number of procedures that one performs with direct supervision, akin to the same training advocated for GI trainees[52].…”
Section: Discussionsupporting
confidence: 85%
“…For studies involving flexible sigmoidoscopy and colonoscopy far fewer randomized controlled trials were available. However, examining the endoscopic outcomes (adenoma, advanced adenoma, colorectal cancer detection and adverse event rates) for non-physicians performing flexible sigmoidoscopy and colonoscopy we discovered that these outcomes for nonphysicians were in line with published data on physicians[4551] suggesting that the patients included in our studies were very likely similar to the patients included in other studies involving physicians performing endoscopy. Finally, minimal data was available on the optimal method used to train non-physicians, but data suggests it may be comparable to the number of procedures that one performs with direct supervision, akin to the same training advocated for GI trainees[52].…”
Section: Discussionsupporting
confidence: 85%
“…Many reports indicated that aging and male sex were risk factors for colonic neoplasia, including adenoma and cancer [18][19][20][21][22][23][24][25][26][27]. Although our results support previous findings on aging, we found female sex to be a risk factor for high-grade dysplasia or carcinoma, which seems to contradict prior reports.…”
Section: Discussioncontrasting
confidence: 83%
“…Two reports, however, that analyzed endoscopically resected lesions only (i.e. except invasive cancer) indicated that the prevalence of highgrade dysplasia was similar between male and female patients [8,9], although many other reports that analyzed lesions including invasive cancer indicated that the prevalence of advanced neoplasia (including invasive cancer) was higher in male patients [18][19][20][21][22][23][24][25][26]. This suggests that adenomas in women may not easily develop beyond high-grade dysplasia into invasive cancer.…”
Section: Discussionmentioning
confidence: 90%
“…These data may change in the future due to the advent of new technological approaches and, in particular, chromo-and magnifying endoscopy as well as confocal laser endoscopy. The cumulative incidence of new adenomas within 3 years after normal endoscopy averages about 7% by flexible sigmoidoscopy and 27% by colonoscopy 82,86 . However, the true incidence rate is hard to estimate exactly, as it depends strongly on the definition used for diagnosis and selection criteria in the populations studied.…”
Section: Prevalencementioning
confidence: 99%